Fiscal Policy and Educational Attainment in the United States : A Generational Accounting Perspective - Xavier Chojnicki; Frédéric Docquier (Institute for the Study of Labor (IZA), 2004)
In this paper, we investigate the consequences of the rise in educational attainment on the US generational accounts. We build on the 1995 accounts of Gokhale et al. (1999) and disaggregate them per schooling level. We show that low skill newborns are characterized by a negative generational account (-15.4% of their lifetime labor income) whilst medium and high skill newborns have positive accounts (26.8 and 32.3% of their lifetime labor income). Compared to Gokhale et al., our baseline forecast is more optimistic. Nevertheless, the rise in educational attainment is not strong enough to restore the generational balance. The current fiscal policy generates a long run deficit. Balancing the budget requires increasing taxes (by about 1.2%) or reducing transfers (by about 2.7%). These results are robust to growth and discounting assumptions, to the treatment of education spending. They are sensitive to assumptions about the schooling level of future generations.
Keywords: E62; J24; H6; 330; generational accounting; human capital; fiscal policy; Finanzpolitik; Intergenerative Belastungsrechnung; Bildungsniveau; Humankapital; Schätzung; Vereinigte Staaten